Oral Atenolol versus Propranolol in the Treatment of Infantile Hemangioma - Abdul, Reema; Rafi, Mazhar; Shah, Asif Hussain; Abid, Saud; Rehman, Ammar Abdul; Zulfiqar, Saad (Biological and Clinical Sciences Research Journal, 2025)
Infantile hemangiomas (IH) are the most common benign vascular tumors of infancy. Propranolol has been established as the first-line therapy; however, its adverse effects have prompted the search for safer alternatives. Atenolol, a selective β-1 blocker, has been suggested to offer similar efficacy with fewer side effects. This study compared the efficacy and safety of propranolol and atenolol in treating problematic IHs in Pakistani infants. Objective: To evaluate and compare the therapeutic efficacy and safety profiles of oral propranolol and atenolol in infants with IH. Methods: A randomized controlled trial was conducted at the Department of Pediatric Surgery, Sheikh Zayed Hospital, Rahim Yar Khan, from December 2024 to May 2025. A total of 120 infants with problematic IHs were randomly assigned to propranolol (n=60) or atenolol (n=60). Propranolol was initiated at 1 mg/kg/day in two divided doses and subsequently increased to 2 mg/kg/day. Atenolol was started at 0.5 mg/kg/day once daily and subsequently increased to 1 mg/kg/day. Treatment duration was six months. The primary outcome was complete/near-complete involution (PGA-5: ≥90% improvement). Secondary outcomes included time to PGA-5 and incidence of adverse events. Data were analyzed using SPSS v25, employing chi-square and t-tests, with p < 0.05 considered significant. Results: Of the 120 infants (mean age 5.2 ± 2.1 months; 56.7% females), 70% in the propranolol group and 63.3% in the atenolol group achieved PGA-5 (p=0.41). The mean time to PGA-5 was 14.2 ± 3.5 weeks for propranolol and 15.0 ± 3.7 weeks for atenolol (p=0.23). Adverse events were significantly higher in the propranolol group (18.3%) compared with the atenolol group (6.7%) (p = 0.048). Most adverse events were mild and manageable, with no life-threatening complications. Conclusion: Both propranolol and atenolol were effective for treating infantile hemangiomas. While propranolol showed slightly higher rates of complete involution and faster response, atenolol demonstrated a safer profile with fewer adverse effects. Atenolol may serve as a viable alternative for infants at risk of propranolol-related complications.